Low-Cost Ergonomic Interventions to Reduce Risk Factors for Work-Related Musculoskeletal Disorders in the Denture Fabrication Workforce - Mega Cattleya P.A. Islami; Rizqi Novita Sari; Sinta Dewi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
To reduce risk factors for work-related musculoskeletal disorders (WMSDs) in the denture fabrication workforce, low-cost ergonomic interventions can be highly effective. This study aims to identify the risk of musculoskeletal disorders in the laboratory of PT X and reduce, enhancing worker comfort, productivity, and overall well-being. Using quantitative methods through RULA and REBA, as well as analysis of the ErgoFellow application, it was found that more than 50% of workers experienced musculoskeletal symptoms in the neck, shoulders, upper back, and wrists in the last 12 months. The Nordic Body Map questionnaire showed discomfort in most respondents due to their work. The results of the work posture analysis showed that the casting and sun-blasting workstations had a score of 4 with a moderate risk profile. In contrast, the night cooling workstation had the highest score of 6 with a moderate risk profile, indicating the need for further improvement. The night cooling station in particular requires investigation regarding the lowering of the stove position and adjustment of the pan position to reduce the risk to the arms and shoulders and improve safety. These recommendations are expected to improve working conditions and mitigate musculoskeletal risks at PT X.